PRODUCTION INDOLE ACETIC ACID ( IAA ) BY BACTERIA USING LOCAL MEDIA - Tariq KALAF; H. FRAHAN; J. AL- KUBAIS; A. AL- ASSAFFII (مجلة جامعة الانبار للعلوم الصرفة, 2012)
ABSTRACT:This study was included isolation and identification of bacterial isolates for growth promoter production (Indol Acetic Acid) by application of local culture and evaluate its efficiency. According to this perpoute bacterial isolates were and examined for their ability to indol production, and then serial labrotory experiments were converted to examine ability of selective isolates for indol production. The local culture used included dry powder of legume, bean, soybean, seed and milk powder. Its also was tested the effect of edition of supplements to the culture such as treptophan, N. broth, glucose, N and P on indol production optimum condition was included such as pH speed of shaking, Inoculums volume, incubation time, temperature, periods of storage to increase production efficiency.This study have the following results: 18 isolates were obtain capable for them indol production (30 from total isolates) 14 isolates were nodulan bacteria .8 isolates which have high efficancy in indol production were tested six isolates tended to Rhizopium and two isolate to Pseudomonus in next screening used culture with special condition, two isolates Pssp2S, Rsp8RA were selected to be used in the following epperinets. When we used 10% of local culture prepared from dry powder of legumes, bean, soybean seed, milk powder led to increased of indol production significantly ranged from (30- 50%). Local culture supplements with peptone, NB, glucose, N and P increased the ability of isolates to indol production (40-65%) significantly.The results of optimum condition study showed the best indol production a chaired with R. sp8RA isolat with pH 7.0 ( 39.41 mg IAA / ml and the best shaking speed at 200/ min without aeration of media 42.2 mg IAA/ ml, the best interaction between the inoculation volume with incubation time with 3 ml/ 100 ml of media at 24 hr of incubation (42.8 mg IAA/ ml) in microbial population 8.41 Log cfu/ ml. Effect of temperature and period of filtrated isolates storage on speed of seed germination increased efficacy filtrated isolates that stored at 4C and 25C for one day and that stored at 4 ◌ْC for 45 days. When it compared with treatment filtrated storage at 25 ◌ْC for 45 days and treatment of industrial indol.The filtrated isolates achieved in commonly increase in speed and percentage of germination was reached 10 – 20 % in temporal differences 3 – 5 day respectively when compare with control treatment.